RENACED-DT1: A National Type 1 Diabetes Registry Initiative in Mexico - Raquel N. Faradji; Marisol Valenzuela-Lara; Maricela Vidrio-Velázquez; Alicia E. Yepez-Rodríguez; Guillermo González-Galvez; María E. Sainz de la Maza-Viadero (Instituto Nacional de Salud Pública, 2020)
Not available